Exome sequencing reveals frequent inactivating mutations in ARID1A, ARID1B, ARID2 and ARID4A in microsatellite unstable colorectal cancer. Issue 3 (13th January 2014) - Cajuso, Tatiana; Hänninen, Ulrika A.; Kondelin, Johanna; Gylfe, Alexandra E.; Tanskanen, Tomas; Katainen, Riku; Pitkänen, Esa; Ristolainen, Heikki; Kaasinen, Eevi; Taipale, Minna; Taipale, Jussi; Böhm, Jan; et al.
<x xml:space="preserve">Abstract</x> ARID1A has been identified as a novel tumor suppressor gene in ovarian cancer and subsequently in various other tumor types. ARID1A belongs to the ARID domain containing gene family, which comprises of 15 genes involved, for example, in transcriptional regulation, proliferation and chromatin remodeling. In this study, we used exome sequencing data to analyze the mutation frequency of all the ARID domain containing genes in 25 microsatellite unstable (MSI) colorectal cancers (CRCs) as a first systematic effort to characterize the mutation pattern of the whole ARID gene family. Genes which fulfilled the selection criteria in this discovery set (mutations in at least 4/25 [16%] samples, including at least one nonsense or splice site mutation) were chosen for further analysis in an independent validation set of 21 MSI CRCs. We found that in addition to ARID1A, which was mutated in 39% of the tumors (18/46), also ARID1B (13%, 6/46), ARID2 (13%, 6/46) and ARID4A (20%, 9/46) were frequently mutated. In all these genes, the mutations were distributed along the entire length of the gene, thus distinguishing them from typical MSI target genes previously described. Our results indicate that in addition to ARID1A, other members of the ARID gene family may play a role in MSI CRC.